Design and analysis of a vertical axis wind turbine - Chue, Wai Yong. (2013)
In the past three decades, increasing attention has being put into wind turbines as a clean and green renewable energy alternative to fossil fuels. There are two main types of wind turbines, the Horizontal Axis Wind Turbine (HAWT) and Vertical Axis Wind Turbine (VAWT). Due to the advantages that the VAWT has over the HAWT in urban environments, this project serves to investigate on an experimental Delta Blade VAWT.